Male circumcision for HIV prevention - a cross-sectional study on awareness among young people and adults in rural Uganda - Hizaamu Ramadhan NB; Miiro-Nakayima Flavia; Wilcken Andrea; Keil Thomas; Balaba-Byansi Dorothy (BMC, 2010)
Abstract Background Medical male circumcision is now part of a comprehensive approach to HIV prevention. It has been shown that awareness of the protective effect of male circumcision leads to high acceptability towards the introduction of medical male circumcision services within countries. The objective of this survey was to identify factors determining awareness of male circumcision for HIV prevention. Methods We interviewed 452 participants (267 adults >24 years of age; 185 youths 14-24 years) living in three rural Ugandan districts in 2008. Using a standardized questionnaire, we assessed socio-demographic parameters, awareness of MC for HIV prevention, general beliefs/attitudes regarding MC and MC status. Determinants for awareness of MC for HIV prevention were examined with multiple logistic regression models. Results Out of all adults, 52.1% were male (mean ± SD age 39.8 ± 11 years), of whom 39.1% reported to be circumcised. Out of all youths, 58.4% were male (18.4 ± 2.5), 35.0% circumcised. Adults were more aware of MC for HIV prevention than youths (87.1% vs. 76.5%; p = 0.004). In adults, awareness was increased with higher educational level compared to no school: primary school (adjusted OR 9.32; 95%CI 1.80-48.11), secondary (5.04; 1.01-25.25), tertiary (9.91; 0.76-129.18), university education (8.03; 0.59-109.95). Younger age and male sex were further significant determinants of increased awareness, but not marital status, religion, district, ethnicity, employment status, and circumcision status. In youths, we found a borderline statistically significant decrease of awareness of MC for HIV prevention with higher educational level, but not with any other socio-demographic factors. Conclusions Particularly Ugandans with low education, youths, and women, playing an important role in decision-making of MC for their partners and sons, should be increasingly targeted by information campaigns about positive health effects of MC.